(untitled) (Fiep Bulletin - online, 2013)
The decurrently sedentary of the technological advance brought obtains the appearance of a group of called illnesses hypocinetic, amongst which the obesity is the most prevalent (Pollock et al., 1986; Mellerowicz & Meller, 1979), bringing I obtain some illness . In this context the intention of this study was to evaluate the effect of swimming in the reduction of the weight, the IMC and the percentage of fat in children. The sample consisted of 22 children of the feminine sex, with age of 07 the 10 years. They had been divided in two randomizations groups, being experimental group I (GE), 11 practicing children of swimming; e group II has controlled (GC), 11 not practicing children of swimming. The experimental group participated of lessons of swimming with frequency of 03 times per week, with the time of 60 minutes of lesson, with monitored cardiac frequency with 60%, during 08 weeks. The corporal composition was evaluated using the IMC and the Protocol of Slaughter, in the daily pay and after test, in the two groups. The analysis statistics was made using the not-parametric test of the addition of ranks of Wilcoxan for two independent samples that is equivalent to test V of Mann-Whitney that if they find in package SPSS. After 08 weeks groups I and II had been compared between itself, not having significance in the corporeal weight, IMC and percentage of fat. The results suggest that swimming in the period of 08 weeks is not enough to promote the reduction of the IMC, corporeal and percentile weight of fat in children of 07 the 10 years of age, of the feminine sex. The physical activity (swimming) associate to one has controlled dietary seems to be method of choice for the reduction of the percentage of fat .